"Balance-Sheet" City: Martin Wagner and the Visualization of Statistical Data. (March 2020) - Vallye, Anna
Martin Wagner (1885-1957) was a leading city planner of the Weimar Republic and chief planner for Greater Berlin from 1926 to 1933. This essay addresses the role of statistical data visualizations in early twentieth-century planning and, specifically, in Wagner's conception of the city as a financial organism subject to managerial-governmental intervention. I argue that for Wagner modern techniques of social data calculation and representation, such as the balance sheet and the graph, became key instruments of planning by translating urban territory into an avatar of the metropolitan economy. Heuristic devices, such "paper cities" of data also had a rhetorical function, both in Germany and in the United States, Wagner's adoptive home after 1938—serving to publicize planning expertise and frame the discipline's intellectual and political legitimation.